2017
DOI: 10.1002/jmor.20636
|View full text |Cite
|
Sign up to set email alerts
|

Development of cranial muscles in the actinopterygian fish Senegal bichir,Polypterus senegalusCuvier, 1829

Abstract: Polypterus senegalus Cuvier, 1829 is one of the most basal living actinopterygian fish and a member of the Actinopterygii. We analyzed the spatial and temporal pattern of cranial muscle development of P. senegalus using whole-mount immunostaining and serial sectioning. We described the detailed structure of the external gill muscles which divided into dorsal and ventral parts after yolk exhaustion. The pattern of the division is similar to that of urodeles. We suggest that, the external gill muscles of P. sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 57 publications
5
33
0
1
Order By: Relevance
“…The same pattern is shown by our ontogenetic series of Acipenser . We observed first muscle differentiation in the opercular flap (Figure d) with no clear origin from the dorsal and ventral anlagen, which is very similar to the pattern showed by Noda et al () for Polypterus . Later in ontogeny, the m. hyohyoideus is confluent and appears derived from both anlagen, before the upper portion in even more advanced stages attaches to the subopercle to form the m. opercularis .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The same pattern is shown by our ontogenetic series of Acipenser . We observed first muscle differentiation in the opercular flap (Figure d) with no clear origin from the dorsal and ventral anlagen, which is very similar to the pattern showed by Noda et al () for Polypterus . Later in ontogeny, the m. hyohyoideus is confluent and appears derived from both anlagen, before the upper portion in even more advanced stages attaches to the subopercle to form the m. opercularis .…”
Section: Discussionsupporting
confidence: 89%
“…Recently Noda et al () concluded that the m. hyohyoideus in Polypterus senegalus , another basal actinopterygian, is derived from the dorsal hyoid constrictor anlage and therefore not homologous to that of other actinopterygians. However, in a recent paper (Konstantinidis et al, ) it was shown, that in Lepisosteus osseus , the m. hyohyoideus covers the entire opercular membrane in larvae around 10 mm NL.…”
Section: Discussionmentioning
confidence: 99%
“…In most amphibians investigated by Ziermann (), the mandibular and hyoid arch muscles develop more or less simultaneously, with a delay in the development of the branchial arch muscles. The hypobranchial muscles also usually develop later than the mandibular and hyoid arch muscles in N. forsteri and amphibians (present study; Ericsson et al, ; Ziermann, ), as well as in the small‐spotted catshark Scyliorhinus canicula (Ziermann et al, ) and the Senegal bichir Polypterus senegalus (Noda et al, ), with what we assume to be the ancestral condition for gnathostomes.…”
Section: Ontogeny/phylogenysupporting
confidence: 70%
“…This evidence taken all together-the large number of soft tissue similarities between extant amphibians and extant lungfishes, the sister group relationship between lungfishes and tetrapods supported by molecular data, the large genome, and the disturbed thyroid axis-all support the hypothesis that living lungfishes are neotenic (see also Bemis, 1984;Joss, 1998Joss, , 2006Long, 1993;Smith, 1977). hyoid muscles (Xenopus: Ziermann & Olsson, 2007), or after the hyoid muscles but simultaneously with mandibular muscles (Polypterus senegalus: Noda et al, 2017). However, most commonly extrinsic eye muscles are the last to show fiber development (Neoceratodus forsteri, caudates, anurans, Monodelphis domestica: present study ;Ericsson et al, 2010;Smith, 1994;Ziermann, 2008).…”
Section: P a E Dom Or P Hosi Smentioning
confidence: 69%
“…Several teleost fish species have already been identified as animal models for craniofacial research. This includes zebrafish (Yelick and Schilling, ; Stock, ; Mork and Crump, ), medaka (Kimura et al, ; Atukorala et al, ; Witten et al, ), cichlids (Fraser et al, ; Powder and Albertson, ), stickleback (Kimmel et al, ; Ellis et al, ), carp (Gidmark et al, , ), Polypterus (Vandenplas et al, ; Noda et al, ) and many others (Meredith and Butler, ; Ferry et al, ; Staab et al, ; Lyon et al, ; Edds‐Walton et al, ; Fritsch et al, ; Thiery et al, ).…”
Section: Introductionmentioning
confidence: 99%